Fast in-frame coding algorithm for HEVC based on probability of mode selection - Ban, Doan Tien; Tropchenko, A.A. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2020)
Subject of Research. The in-frame encoding process in the standard of high-efficiency encoding of video images is considered. The analysis of mode selection probability is carried out; the algorithm of fast prediction mode selection is proposed. Method. It is proposed to select a set of 11 modes with the highest probability of selection of the 35 possible modes of the standard “default” algorithm, as input data for further refined selection. Depending on the results obtained, another stage is added, where the choice is reduced up to 4 modes. The selected modes are used in a two-step optimization process, which selects the best mode for the current encoding block. Main Results. The proposed algorithm is implemented in the C++ development environment. A number of standard video sequences with four quantization parameter values is used for testing. The results of the carried out experiments show that the proposed fast algorithm reduces the encoding time by 17.03 % compared to HM-16.20 reference software, with an increase in transmission speed by 1.26 % and a loss of quality only by 0.033 dB. Practical Relevance. The proposed fast algorithm provides a reduction in computational costs with an extremely negligible loss of quality of the restored video sequence. It can be used as a standard H265 video codec block for replacement of the existing in-frame prediction block in the reference program to speed up the video compression process.